Self-Diagnosis of Psychopathy Portrayed in the End of the F***Ing World Series - Nur Karimah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
In contemporary media, characters who self-diagnose with psychological disorders often reflect deeper emotional and psychological complexities rather than clinically accurate conditions. One compelling example is found in the British dark comedy-drama series The End of The F**ing World*, where James claims to be a psychopath. However, this self-diagnosis raises critical psychological questions: Is James truly incapable of empathy, or is his label a defense mechanism masking unresolved trauma from his childhood? By applying Sigmund Freud’s psychoanalytic theory—particularly the structural model of personality (id, ego, superego)—alongside Anna Freud’s theory of defense mechanisms, this study investigates the role of self-diagnosis not as an objective or medically valid truth, but as a psychological shield to avoid emotional vulnerability and confrontation with repressed pain. James' behaviors are analyzed through selected scenes and dialogues in the series, with additional triangulation from the original graphic novel to support the interpretation. The analysis reveals that James’ declaration of being a psychopath aligns more with mechanisms such as repression, projection, and emotional numbing, rather than the clinical criteria of psychopathy. His emotional detachment is revealed to be a constructed barrier stemming from maternal loss, neglect, and fear of connection. The study concludes that self-diagnosis in this context acts as a subconscious strategy to cope with unresolved trauma and to maintain psychological equilibrium amid inner conflict. This case exemplifies how fictional representations can mirror real-life struggles with identity, mental health, and the desire to label complex emotions through simplified diagnostic terms, especially in youth who lack proper support systems.